STRATEGI PENGEMBANGAN KULINER TRADISIONAL BETAWI DI DKI JAKARTA - Dhian Tyas Untari; Dudung Darusman; Joko Prihatno; Harnios Arief (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
Betawi is a reflection of the acculturation process of several tribes in Indonesia and even some nations in the world. But in fact, the existence of Betawi Culinary Culture is now starting eroded by the concept of modernization. Culinary is one of the cultural products of a society, as well as Betawi Culinary. Where now aday Betawi Culinary is not a superior culinary in Jakarta. Thus it is necessary to made a business revitalization strategy in developing traditional culinary (Betawi) in Jakarta. Thus in general purpose of the research is to build Betawi Culinary development strategy in Jakarta, so the Traditional Betawi Culinari, will clasified on 3 classification; Familiar Culinary, Recall Culinary and Past Known Culinary. Quantitaive Metode used; EFAS/IFAS matrix, Grand Matris and SWOT. Pairwise comparing and eigenfactor score used as a referral to giving equal weight on EFAS/ IFAS matrix. Result of the study show that cross-sectoral coordination, Strengthening the marketing system and increase the economic value of Betawi Culinary are needed to increasing the existence of culinary betawi in global market. The results expected to be reference for any relevant agencies in develomping traditional culinary as a culture product.